1995
DOI: 10.1002/app.1995.070571302
|View full text |Cite
|
Sign up to set email alerts
|

Study of radical copolymerization of tetrafluoroethylene with ethylene in suspension

Abstract: SYNOPSISRadical copolymerization of tetrafluoroethylene (TFE) with ethylene (E) was initiated by 2,2'-azo-bis-isobutyronitrile in batch and semibatch operation. The effect of reaction conditions (temperature, pressure, stirring speed, molar ratio of monomers, etc.) on copolymerization rate and copolymer molecular weight was studied. The highest reaction rate was observed at TFE content over 70 mol % and was found to be proportional to initiator concentration and total monomer content by powers of 0.9 and 1.54,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…No other changes in the IR spectra were observed, which indicated that the functional groups, such as C(O)F, COOH, CFCH, etc., typical for the thermal destruction of the fluoropolymers, were not formed. Similar trends were observed with the study of the mechanical characteristics of alternating copolymers after the exposure to thermal ageing under static or dynamic conditions 15…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…No other changes in the IR spectra were observed, which indicated that the functional groups, such as C(O)F, COOH, CFCH, etc., typical for the thermal destruction of the fluoropolymers, were not formed. Similar trends were observed with the study of the mechanical characteristics of alternating copolymers after the exposure to thermal ageing under static or dynamic conditions 15…”
Section: Resultssupporting
confidence: 84%
“…These processes favored the formation of more regular structure, which, in turn, affected the thermal stability of the TFE‐E copolymers. As a result, the difference between the decomposition and melting temperatures exceeded 100 K 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are rather low compared to that of heterophase reactions of TFE with ␣-olefins, 52 for which E a Ͼ 80 kJ ⅐ mol…”
Section: Determination Of the Reaction Orders And Of The Activation Ementioning
confidence: 85%